New algorithm for gyroless spacecraft angular rate Estimation and its application - Abdelrahman, Mohammad; Samaan, Malak A. (2006)
A new algorithm for estimating the angular velocity using quaternion measurements is developed based on the concept of the global optimality resulting when using a centralized or master Kalman filter. The new filter consists of three local Kalman filters run in parallel. Each of them feed a master filter with its output estimates. The master filter then runs for global optimal estimate of the angular velocity. The master filter estimate and error covariance is fed back to update a main Kalman filter which in turn fed back its estimates to update two other secondary Kalman filters. The new algorithm performance is investigated and tested against other two filters and has shown much better results when using in both modes (quaternion measurement/low pass filter). The study is concluded by the application of the concept of estimating the angular velocity vector during the detumbling mode of a spacecraft. The simulation results have shown great improvements in the detumbling efficiency since under the same control torque constraints the spacecraft derived to almost null angular velocity in a shorter time than when using the traditional control approaches applied during this mode.